Advances in ergonomics of manufacturing managing the enterprise of the future : proceedings of the AHFE 2017 International Conference on Human Aspects of Advanced Manufacturing, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences 2017 Los Angeles, Calif.); Trzcielinski, Stefan (Cham Springer International Publishing, 2018)
This book discusses the latest advances in people-centered design, operation, and management of broadly defined advanced manufacturing systems and processes. It reports on human factors issues related to various research areas such as intelligent manufacturing technologies, web-based manufacturing services, digital manufacturing worlds, and manufacturing knowledge support systems, as well as other contemporary manufacturing environments. The book covers an extensive range of applications of human factors in the manufacturing industry: from work design, supply chains, evaluation of work systems, and social and organization design, to manufacturing systems, simulation and visualization, automation in manufacturing, and many others. Special emphasis is given to computer aided manufacturing technologies supporting enterprises, both in general and in the manufacturing industry in particular, such as knowledge-based systems, virtual reality, artificial intelligence methods, and many more. Based on the AHFE 2017 International Conference on Human Aspects of Advanced Manufacturing, held on July 17-21, 2017, in Los Angeles, California, USA, the book provides readers with a timely snapshot of the enterprises of the future and a set of cutting-edge technologies and methods for building innovative, human-centered, and computer-integrated manufacturing systems.
Advanced real-time weld monitoring evaluation demonstrated with comparisons of manual and robotic TIG welding used in critical nuclear industry fabrication -- Measuring the human aspect: The key for managing the complexity in production -- Predicting human cycle times in robot assisted assembly -- Development and characterization of hybrid composites from textile waste -- Managing the human factor during the working-out of new technologies and hardware: The reindustrialization conditions -- Organizations in era of digital culture -- How enterprises identify market opportunities: Research results and findings -- Age-differentiated analysis of the influence of introduction methods on learning sensorimotor tasks -- World class remanufacturing production systems: An analysis of Mexican maquiladoras -- Relationship between lean manufacturing and ergonomics -- Macroergonomic compatibility index for manufacturing systems. A case study -- Investigation of evaluation method for braiding strings -- Diagnostic tool to examine enterprise capacity in the area of disability management -- Expert skill of injection molding -- a new composite processing, DFFIM -- Worker's skill comparison and motion analysis -- A comparison of transition of tool gripping force between expert and non-expert during deburring processes.
Includes bibliographical references and index.
E-3262G donated by Dr. Aura C. Matias.
Keywords: Manufacturing processes -- Human factors -- Congresses; Production management; Artificial intelligence; Computer-aided engineering; Manufacturing industries